2021
DOI: 10.1111/desc.13181
|View full text |Cite
|
Sign up to set email alerts
|

Prior task experience increases 5‐year‐old children's use of proactive control: Behavioral and pupillometric evidence

Abstract: Children engage cognitive control reactively when they encounter conflicts; however, they can also resolve conflicts proactively. Recent studies have begun to clarify the mechanisms that support the use of proactive control in children; nonetheless, sufficient knowledge has not been accumulated regarding these mechanisms. Using behavioral and pupillometric measures, we tested the novel possibility that 5‐year‐old children (N = 58) learn to use proactive control via the acquisition of abstract task knowledge th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…In particular, Yanaoka et al. (2022) reported that prior task experience influences engagement of proactive control at age 5, suggesting that young children may learn to use proactive control through the acquisition of abstract task knowledge that captures regularities of the task. Berger & Grosse Wiesmann (2022) reported a facilitation effect of positive emotion on conflict processing in 2‐ to 7‐year‐olds, hence suggesting that positive emotion can already trigger efficient control processes from early stages of self‐regulation development.…”
mentioning
confidence: 99%
“…In particular, Yanaoka et al. (2022) reported that prior task experience influences engagement of proactive control at age 5, suggesting that young children may learn to use proactive control through the acquisition of abstract task knowledge that captures regularities of the task. Berger & Grosse Wiesmann (2022) reported a facilitation effect of positive emotion on conflict processing in 2‐ to 7‐year‐olds, hence suggesting that positive emotion can already trigger efficient control processes from early stages of self‐regulation development.…”
mentioning
confidence: 99%
“…However, the transfer of temporal aspects of task knowledge has been demonstrated only in adults. Yanaoka et al (2022) did not provide clear evidence that 5-year-olds can use their knowledge of the temporal structure of activation of task goals to support their subsequent engagement of proactive control.…”
mentioning
confidence: 86%
“…Second, we predicted that adults (Experiment 1) and schoolaged children (Experiment 2) in the proactive possible training group would respond more quickly in the test phase than in the training phase, suggesting that they engage proactive control more efficiently at test following training; that is, positive transfer would occur. This second prediction is based on the evidence that practice with cued task-switching might simply help 5-year-olds shift towards proactive control in a subsequent cued task-switching condition (Yanaoka et al, 2022) Importantly, as suggested by Bhandari and Badre (2018), it is possible that both positive and negative transfer effects would transiently occur during the initial trials of the test phase and rapidly decrease across subsequent trials.…”
Section: Experiments 1 Andmentioning
confidence: 99%
See 2 more Smart Citations